An activatable near-infrared hemicyanine-based probe for selective detection and imaging of Hg2+ in living cells and animals. Issue 13 (7th June 2022) - Li, Min; Li, Ruiyu; Chen, Xuefei; Liu, Jin; Shao, Yong; Xu, Zhiai; Zhang, Wen
Abstract : A near-infrared hemicyanine-based probe (CyP ) was designed for selective detection and imaging of Hg 2+ in living cells and animals. Abstract : Fluorescence imaging in the near-infrared (NIR) window has great potential for clinical diagnosis and treatment because of its deep penetration and high contrast. Here, a NIR hemicyanine-based probe (CyP ) was synthesized for selective detection and imaging of Hg 2+ in living cells and animals. Using the rigid xanthene structure as the electron donor, trimethylindolenine as the electron acceptor and diphenylphosphinothioic chloride as the recognition element, the probe CyP could specifically respond to Hg 2+ and transform into an activated donor–π-acceptor (D–π-A) motif with a NIR emission maximum at 710 nm. Cell and animal imaging experiments showed that the probe CyP could be activated by Hg 2+ and had good concentration dependence in imaging. Meanwhile, animal imaging experiments showed that the activated CyP probe exhibited a higher tissue penetration depth and spatiotemporal resolution. Thus, the probe CyP could be a useful tool for monitoring and visually evaluating Hg 2+ in living systems.